Multivariate Study of Inulin Addition on the Quality of Sponge Cakes - Zbikowska Anna; Marciniak-Lukasiak Katarzyna; Kowalska Malgorzata; Onacik-Gür Sylwia (Polish Journal of Food and Nutrition Sciences)
The aim of the study was to determine the possibility of reducing fat content in fatty sponge-cake products by addition of inulin. 200 g/kg, 440 g/kg, 680 g/kg and 100% of fat was substituted with 20 g/kg, 35 g/kg, 50 g/kg, and 62.5 g/kg of inulin, respectively. The authors used two types of fat: with low and high content of trans isomers – containing 2.1 g/kg and 511.2 g/kg of fatty acid methyl esters (FAME), respectively. An analysis of crumb quality and the evaluation of sensory discriminants were undertaken.